Effect Of Zinc And Ingredients Of Protein Supplement On Sperm Parameters And Male Reproductive Hormones- An RCT Study - Safdar, Saira; Mughal, Irfan Afzal; Ain, Noor Ul; Jabeen, Sidra; Farooq, Muhammad Hassaan; Irfan, Asma (Journal of Rawalpindi Medical College, 2023)
Objective: The purpose of this study was to assess the protective effects of zinc against injury to sperm parameters and male reproductive hormones brought on by toxic protein supplement constituents. Methods: 30 male Sprague Dawley rats were used in the study, of which 10 were in Group 1 (given standard laboratory food), 10 were in Group 2, fed standard laboratory food nutritional supplement powder and 10 were in Group 3, fed standard laboratory food, nutritional supplement powder and zinc. Semen Analysis of Male Sprague Dawley rats of all 3 groups was evaluated after 8 weeks. Sperm parameters and serum levels of Male Reproductive Hormones were measured at the beginning and the end of the study. Results: There was a significant decrease (P<0.05) in Mean ± SEM of sperm count millions /ml, sperm motility (%), and normal sperm morphology (%) in Group 2 rats when compared with Group 1. Zinc supplement in Group 3 caused a significant increase (P<0.05) in Mean ± SEM of sperm parameters including sperm count millions /ml, sperm motility (%) and normal sperm morphology (%) as compared to Group 2 rats. Mean ± SEM of serum level of testosterone Hormone, Follicle Stimulating Hormone(FSH), and Luteinizing Hormone(LH) of Group 2 rats showed a significant (P<0.05) decrease when compared with Group 1 rats. However, the use of Zinc in Group 3 rats significantly (P<0.05) increased serum Testosterone, FSH, and LH levels when compared to Group 2. No significant difference was noted between serum levels of Testosterone, in Group 1 and Group 3. Serum levels of FSH and LH in Group 3 rats (484.81+ 78.17 ng/ml) were significantly increased (P<0.05) as compared to Group 1 rats. Conclusion: Regular addition of antioxidant Zinc with protein supplements has the potential to restore normal functions of the male reproductive system. Keywords: Protein supplements, Soy Protein, Silicon dioxide, Zinc, Sperm parameters, Testosterone, Follicle stimulating hormone, Luteinizing hormone.